EFFECT AND COMPARISON OF RECYCLING AND STAGNANT FRESHWATER ON PERFORMANCES (GROWTH AND SURVIVAL RATES; FISH QUALITY) AND PROFITABILITY OF THE ORNAMENTAL FISH Barbus schwanefeldi (KAPIAT) REARED AT 4 DIFFERENT DENSITIES - Sudarto Sudarto; Agus Priadi; Jack Slembrouck; Laurent Pouyaud; I Wayan Subamia (Indonesian Aquaculture Journal, 2007)
Comparing two different rearing systems in fish production through stagnant and recirculation water systems showed that recirculation system has several benefits such as reducing manpower, and minimize or eliminate in using antibiotics and also eliminate the grow out of diseases, increasing the profits due to increase in density of fish cultured in the system, and water quality remain stable in optimal condition.